Rapid Palatal Expansion Should Not Be Trivialized: Two Case Reports of Unexpected Complications - Lopponi, Gaia; Maino, Bortolo Giuliano; Dalessandri, Domenico (European Journal of Dentistry, 2021)
Rapid maxillary expansion is one of the most common orthodontic procedures performed in the pediatric population, easy to accomplish and compliance free, therefore really effective. Nevertheless, a careful diagnosis and frequent clinical follow-up appointments are necessary during the first weeks of active treatment. The purpose of this article was to report two cases of unexpected complications during orthopaedic maxillary expansion, involving two 7-year-old female patients, one presenting a saddle nose with suborbital hematoma and the other one an asymmetric palatal expansion. In both cases, the clinical situation progressively relapsed during the months following expansion appliance removal.
Keywords: rapid maxillary expansion; orthodontic; orthopaedic; pediatric; complications